Penggunaan Adenin Sulfat Pada Perbanyakan Mikro Talas Jepang - W Hattu; Dj. F Parera; Simos H.T Raharjo (Agrologia, 2018)
Taro is a staple food source in several regions of Indonesia. One type of this crop, namely Japanese taro or satoimo [Colocasia esculenta (L.) Schott var. antiquorum], is widely consumed in Japan so that there are export opportunities into the country. To overcome the problem of lack of propagules in the cultivation of taro, quality seed production can be done with micro propagation. This study aimed to obtain MS tissue culture media with the right concentration of adenine sulfate for Japanese taro micro propagation. The study was designed as a single factor experiment with a Completely Randomized Design, with an experimental factors of adenine sulfate concentration consisting of 5 levels, namely: A0 (control, 0 mg / l), A1 (10 mg / l), A2 (60 mg / l ), A3 (110 mg / l), A4 (160 mg / l), and with 5 replications. The use of MS media with BAP 0.5 mg /l + adenine sulfate 160 mg/l gave the best results for shoot multiplication with an average number of shoots produced 21.40 per culture bottle, at 12 weeks after culturing. The success percentage of plantlet acclimatization was 86%, and tissue cultur propagules subsequently was able to grow normally under ex vitro conditions.